Organic covalent material and preparation method thereof, composite adsorption film and preparation method and application thereof

By preparing organic covalent materials and chitosan in organic solvents to make a composite adsorption film, the composite adsorption films are solved, and the composite films in the prior art have low strength, poor stability, low adsorption amount and complex preparation effects are achieved, and the effect of efficient adsorption of heavy metal ions and recycling is achieved.

CN119751784AActive Publication Date: 2025-04-04ZHIXIN (WUXI) LITHIUM TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411954120.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In the prior art, when treating heavy metal ions in water, the composite film has low strength, poor stability, low adsorption amount, and complex preparation, making it difficult to industrialize.

Method used

The organic covalent material was prepared by mixing 2,5-diaminoterephthalic acid with hydroxyl-containing benzene-1,3,5-triformaldehyde derivatives in an organic solvent, and composited with chitosan to prepare a composite adsorption film. The method includes contact mixing in the presence of an acidic substance, scraping the film treatment and contact mixing with an alkali solution to obtain a composite adsorption film.

Benefits of technology

It realizes efficient adsorption of heavy metal ions, improves adsorption capacity, and is recyclable for composite adsorption film, which is simple to operate and low cost, has green and environmentally friendly characteristics, and is suitable for heavy metal ion recovery field.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of heavy metal ion recovery, and discloses an organic covalent material and a preparation method thereof, and a composite adsorption film and a preparation method and application thereof. The method comprises the following steps: in the presence of an organic solvent, mixing 2, 5-diamino terephthalic acid and a hydroxyl-containing benzene-1, 3, 5-tricarboxaldehyde derivative for reaction to obtain the organic covalent material. The organic covalent material provided by the invention is compounded with chitosan to prepare a composite adsorption film, and the composite adsorption film can be used for adsorbing heavy metal ions in a water body, is high in heavy metal ion adsorption capacity, can be recycled, and has a relatively great application prospect in the field of heavy metal ion recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heavy metal ion recovery, and in particular to an organic covalent material and a preparation method thereof, a composite adsorption membrane and a preparation method and application thereof. Background Art

[0002] Mining and metal smelting processing lead to increased levels of heavy metal ions (such as chromium, lead, mercury, etc.) in water. Heavy metal ions are generally toxic and non-biodegradable. The composition of heavy metal ions in wastewater is complex. Studies have shown that complex interactive complexes will occur between different heavy metal ions and between heavy metal ions and non-heavy metal ion pollutants, forming hybrid pollutants that are more difficult to treat. Nowadays, with the increasing shortage of drinkable fresh water resources, if wastewater containing heavy metal ions is discharged without treatment, it will pose a serious threat to water sources.

[0003] At present, the main methods for treating heavy metal ions in water pollution include chemical precipitation, flocculation precipitation, oxidation, adsorption, reverse osmosis and biotechnology. Adsorption is the most commonly used method for treating heavy metal pollution in water bodies. Natural biological adsorbents are widely used in the treatment of industrial wastewater due to their excellent adsorption effect, low price, recyclability and no secondary pollution. Among them, chitosan (CS) is a natural polysaccharide with the advantages of being renewable, biodegradable and having a large yield. It has an excellent adsorption effect on specific heavy metal ions and has broad application prospects in the field of water treatment.

[0004] CN109021264A discloses a method for preparing a MOFs-chitosan nanofiber composite membrane, wherein chitosan nanofibers are prepared by electrostatic spinning, and then the synthesized MOFs material is blended with the chitosan nanofibers and then compounded under the action of a crosslinking agent to obtain a MOFs-chitosan nanofiber composite membrane, which effectively solves the problems of low strength and poor stability of the MOFs-chitosan nanofiber composite membrane and poor dispersibility of the MOFs material in the chitosan fiber. However, this solution still has the defects of low adsorption capacity, complex preparation and difficulty in industrialization. Summary of the invention

[0005] The object of the present invention is to provide a composite adsorption membrane with high adsorption capacity for heavy metal ions.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing an organic covalent material, which comprises: in the presence of an organic solvent, mixing 2,5-diaminoterephthalic acid with a hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative to obtain the organic covalent material.

[0007] Preferably, the hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde and / or 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde.

[0008] Preferably, the molar ratio of the 2,5-diaminoterephthalic acid to the hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 1-5:1.

[0009] Preferably, the organic solvent is mesitylene.

[0010] Preferably, the mixing reaction is carried out in an inert atmosphere, and the conditions of the mixing reaction include: a temperature of 100-140° C. and a time of 50-70 min.

[0011] The second aspect of the present invention provides an organic covalent material prepared by the method described in the first aspect.

[0012] A third aspect of the present invention provides a composite adsorption membrane, the composite adsorption membrane comprising an organic covalent material and chitosan;

[0013] The organic covalent material is the organic covalent material described in the second aspect.

[0014] Preferably, the organic covalent material accounts for 10-30 wt % of the total mass of the composite adsorption membrane.

[0015] The fourth aspect of the present invention provides a method for preparing the composite adsorption membrane according to the third aspect, the method comprising:

[0016] (1) contacting and mixing the organic covalent material and chitosan in the presence of an acidic substance I to obtain a mixed solution;

[0017] (2) subjecting the mixed solution to a scraping treatment to obtain an intermediate film;

[0018] (3) The intermediate membrane is contacted and mixed with an alkaline solution to obtain the composite adsorption membrane.

[0019] Preferably, in step (1), the acidic substance is acetic acid.

[0020] Preferably, the acidic substance is provided in the form of an acidic substance aqueous solution, and the concentration of the acidic substance aqueous solution is 0.2-0.8 mol / L.

[0021] Preferably, in step (3), the alkaline substance in the alkaline solution is sodium hydroxide and / or potassium hydroxide.

[0022] Preferably, the concentration of the alkaline solution is 5-10 wt %.

[0023] The fifth aspect of the present invention provides use of the composite adsorption membrane described in the third aspect in adsorbing heavy metal ions.

[0024] Through the above technical solution, the present invention has at least the following advantages:

[0025] (1) The organic covalent material provided by the present invention is combined with chitosan to prepare a composite adsorption membrane, which can be used to adsorb heavy metal ions in water. The composite adsorption membrane has a high adsorption capacity for heavy metal ions and can be recycled, and has great application prospects in the field of heavy metal ion recovery.

[0026] (2) The preparation method of the composite adsorption membrane provided by the present invention is simple to operate, low in cost, and environmentally friendly. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] As mentioned above, the first aspect of the present invention provides a method for preparing an organic covalent material, which comprises: in the presence of an organic solvent, mixing 2,5-diaminoterephthalic acid with a hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative to obtain the organic covalent material.

[0029] Preferably, the hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde and / or 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde. The inventors of the present invention have found that in this preferred case, the prepared organic covalent material is applied to a composite adsorption membrane to obtain a composite adsorption membrane with a higher adsorption capacity for heavy metal ions.

[0030] Preferably, the molar ratio of the 2,5-diaminoterephthalic acid to the hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 1-5:1, preferably 2-4:1.

[0031] Preferably, the organic solvent is mesitylene.

[0032] Preferably, the concentration of the 2,5-diaminoterephthalic acid in the starting reaction system for the mixed reaction is 1.5-4 mol / L.

[0033] Preferably, the mixed reaction is carried out in an inert atmosphere, and the conditions of the mixed reaction include: a temperature of 100-140° C., preferably 110-130° C.; and a time of 50-70 min.

[0034] Preferably, the inert atmosphere is nitrogen.

[0035] The method of the present invention may also include post-treatment means known in the art such as washing and drying. For example, the material obtained by the mixed reaction is centrifugally washed with deionized water and then vacuum dried to obtain the organic covalent material. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.

[0036] As mentioned above, the second aspect of the present invention provides an organic covalent material prepared by the method described in the first aspect.

[0037] As mentioned above, the third aspect of the present invention provides a composite adsorption membrane, which comprises an organic covalent material and chitosan; the organic covalent material is the organic covalent material described in the second aspect.

[0038] Preferably, the organic covalent material accounts for 10-30 wt %, preferably 15-25 wt %, of the total mass of the composite adsorption membrane.

[0039] Preferably, the composite adsorption membrane has a thickness of 90-110 μm.

[0040] As mentioned above, the fourth aspect of the present invention provides a method for preparing the composite adsorption membrane according to the third aspect, the method comprising:

[0041] (1) contacting and mixing the organic covalent material and chitosan in the presence of an acidic substance I to obtain a mixed solution;

[0042] (2) subjecting the mixed solution to a scraping treatment to obtain an intermediate film;

[0043] (3) The intermediate membrane is contacted and mixed with an alkaline solution to obtain the composite adsorption membrane.

[0044] Preferably, in step (1), the acidic substance is acetic acid.

[0045] Preferably, the acidic substance is provided in the form of an acidic substance aqueous solution, and the concentration of the acidic substance aqueous solution is 0.2-0.8 mol / L, preferably 0.4-0.6 mol / L.

[0046] Preferably, in step (1), the conditions of the contact mixing I include: temperature of 30-50°C and time of 90-110 min.

[0047] According to a preferred embodiment, the operation of step (1) includes:

[0048] The organic covalent material is dissolved in the acidic substance aqueous solution to obtain an intermediate solution, and then the chitosan is added into the intermediate solution to perform the contact mixing I to obtain the mixed solution.

[0049] Preferably, the method for preparing a composite adsorption film further comprises: before performing step (2), degassing the mixed solution. The present invention has no specific requirements for the method of degassing, and those skilled in the art can select it according to the technical means known in the art, for example, by allowing the mixed solution to stand for degassing.

[0050] According to another preferred specific implementation, in step (2), the mixed liquid is poured onto a substrate, and a scraping knife is used to perform the scraping treatment; more preferably, the substrate is a glass plate.

[0051] Preferably, in step (2), the conditions of the contact mixing II include: temperature of 30-80°C and time of 20-40 min.

[0052] Preferably, in step (3), the alkaline substance in the alkaline solution is sodium hydroxide and / or potassium hydroxide.

[0053] Preferably, the concentration of the alkaline solution is 5-10 wt%, preferably 7-9 wt%.

[0054] The method for preparing the composite adsorption film of the present invention may also include post-treatment means known in the art such as washing and drying. For example, the material obtained by the contact mixing Ⅱ is washed with distilled water and then vacuum dried to obtain the composite adsorption film. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.

[0055] As mentioned above, the fifth aspect of the present invention provides the use of the composite adsorption membrane described in the third aspect in the adsorption of heavy metal ions.

[0056] Preferably, the heavy metal ions include Cd 2+ and Mn 2+ .

[0057] Further preferably, the composite adsorption film is 2+ The ion adsorption capacity of the composite adsorption membrane is ≥17 mg / g, preferably ≥22 mg / g; 2+ The ion adsorption capacity is ≥10 mg / g, preferably ≥12 mg / g, and more preferably ≥16 mg / g.

[0058] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials and equipment used are all commercially available.

[0059] The following preparation examples are used to illustrate the preparation method of the organic covalent material of the present invention.

[0060] Preparation Example 1

[0061] 2,5-Diaminoterephthalic acid and 2,4-dihydroxybenzene-1,3,5-triformaldehyde were dissolved in 500 mL of mesitylene at a molar ratio of 3:1 (the amount of 2,5-diaminoterephthalic acid was 3 mol), placed in a glass microwave tube, filled with nitrogen and sealed for a mixing reaction, reacted at 120°C for 60 minutes, and then centrifuged and washed and vacuum dried in sequence to obtain a powdered organic covalent material COF-1.

[0062] Preparation Example 2

[0063] The method was similar to that of Preparation Example 1, except that an equal molar amount of 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde was used to replace 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde;

[0064] The rest are the same, and a powdered organic covalent material COF-2 is obtained.

[0065] Preparation Example 3

[0066] The method is similar to that of Preparation Example 1, except that the molar amount of 2,5-diaminoterephthalic acid is kept unchanged, and the molar ratio of 2,5-diaminoterephthalic acid to 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde is adjusted to 1:1;

[0067] The rest are the same, and a powdered organic covalent material COF-3 is obtained.

[0068] Preparation Example 4

[0069] The method is similar to that of Preparation Example 1, except that the molar amount of 2,5-diaminoterephthalic acid is kept unchanged, and the molar ratio of 2,5-diaminoterephthalic acid to 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde is adjusted to 2:1;

[0070] The rest are the same, and a powdered organic covalent material COF-4 is obtained.

[0071] Preparation Example 5

[0072] The method is similar to that of Preparation Example 1, except that the molar amount of 2,5-diaminoterephthalic acid is kept unchanged, and the molar ratio of 2,5-diaminoterephthalic acid to 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde is adjusted to 4:1;

[0073] The rest are the same, and a powdered organic covalent material COF-5 is obtained.

[0074] Preparation Example 6

[0075] The method is similar to that of Preparation Example 1, except that the molar amount of 2,5-diaminoterephthalic acid is kept unchanged, and the molar ratio of 2,5-diaminoterephthalic acid to 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde is adjusted to 5:1;

[0076] The rest are the same, and a powdered organic covalent material COF-6 is obtained.

[0077] Preparation Example 7

[0078] The method was similar to that of Preparation Example 1, except that an equal molar amount of 2-hydroxybenzene-1,3,5-tricarbaldehyde was used to replace 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde;

[0079] The rest are the same, and the powdered organic covalent material COF-7 is obtained.

[0080] Comparative Preparation Example 1

[0081] The method was similar to that of Preparation Example 1, except that an equal molar amount of benzene-1,3,5-tricarbaldehyde was used to replace 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde;

[0082] The rest are the same, and a powdered organic covalent material COF-D1 is obtained.

[0083] The following examples are used to illustrate the preparation method of the composite adsorption membrane of the present invention.

[0084] Example 1

[0085] 2 g of COF-1 was dissolved and dispersed in 50 mL of 0.5 mol / L acetic acid aqueous solution to obtain an intermediate solution, and then 8 g of chitosan was added to the intermediate solution to perform contact mixing I (temperature of 30° C., time of 100 min), and mechanically stirred and mixed to obtain a mixed solution;

[0086] The mixed liquid was allowed to stand for degassing, then poured onto a clean and smooth glass plate, scraped with a scraper and placed in a cool place to dry, then placed in an 8wt% alkaline solution (NaOH solution) at 30°C for 30 minutes, rinsed with distilled water, and finally dried in a vacuum drying oven to obtain a composite adsorption film M-1 (thickness 100μm).

[0087] Example 2 to Example 7

[0088] The method was similar to that of Example 1, except that COF-2, COF-3, COF-4, COF-5, COF-6, and COF-7 were used in equal weights to replace COF-1;

[0089] The rest were the same, and composite adsorption membranes M-2, M-3, M-4, M-5, M-6, and M-7 were obtained respectively.

[0090] Example 8

[0091] The method was similar to that of Example 1, except that the weight of COF-1 was adjusted to 5 g;

[0092] The rest were the same, and the composite adsorption membrane M-8 was obtained.

[0093] Comparative Example 1

[0094] The method was similar to that of Example 1, except that an equal weight of COF-D1 was used to replace COF-1;

[0095] The rest are the same, and the composite adsorption membrane M-D1 is obtained.

[0096] Application Examples

[0097] The composite adsorption film (0.25 g) prepared in the example was mixed with 25 mL of heavy metal solution (Cd 2+ Concentration 0.01g / L, Mn 2+ The adsorption amount of heavy metal ions was calculated by atomic absorption spectrometry.

[0098] Adsorption amount (mg / g) = (heavy metal ion concentration before adsorption - heavy metal ion concentration after adsorption) × volume of heavy metal solution / mass of composite adsorption membrane Formula (1)

[0099] In formula (1), the unit of heavy metal ion concentration is mg / L, the unit of volume of heavy metal solution is L, and the unit of mass of composite adsorption membrane is g.

[0100] The calculation results are shown in Table 1.

[0101] Table 1

[0102] <![CDATA[Cd 2+ Adsorption capacity (mg / g)]]> <![CDATA[Mn 2+ Adsorption capacity (mg / g)]]> Example 1 23.93 17.47 Example 2 21.06 13.52 Example 3 22.74 11.95 Example 4 20.73 11.06 Example 5 21.64 12.83 Example 6 23.12 10.55 Example 7 18.64 9.84 Example 8 17.85 9.05 Comparative Example 1 10.56 6.45

[0103] The results in Table 1 show that the organic covalent material provided by the present invention can be combined with chitosan to prepare a composite adsorption membrane with high adsorption capacity. The composite adsorption membrane is effective for heavy metal ions, especially Cd 2+and Mn 2 + The adsorption capacity of the product is significantly better than that of the existing technology, and it has great application prospects in the field of heavy metal ion recovery.

[0104] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an organic covalent material, characterized in that: The method comprises: in the presence of an organic solvent, mixing 2,5-diaminoterephthalic acid and a hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative for reaction to obtain the organic covalent material.

2. The method according to claim 1, characterized in that The hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 2,4-dihydroxybenzene-1,3,5-tricarbaldehyde and / or 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde.

3. The method according to claim 1, characterized in that: The molar ratio of the 2,5-diaminoterephthalic acid to the hydroxyl-containing benzene-1,3,5-tricarbaldehyde derivative is 1-5:

1.

4. The method according to any one of claims 1 to 3, characterized in that: The organic solvent is mesitylene; And / or, the mixed reaction is carried out in an inert atmosphere, and the conditions of the mixed reaction include: a temperature of 100-140° C. and a time of 50-70 min.

5. An organic covalent material prepared by the method according to any one of claims 1 to 4.

6. A composite adsorption membrane, characterized in that: The composite adsorption film comprises organic covalent material and chitosan; The organic covalent material is the organic covalent material according to claim 5.

7. The composite adsorption membrane according to claim 6, characterized in that: The organic covalent material accounts for 10-30 wt % of the total mass of the composite adsorption membrane.

8. A method for preparing the composite adsorption membrane according to claim 6 or 7, characterized in that: The method includes: (1) contacting and mixing the organic covalent material and chitosan in the presence of an acidic substance I to obtain a mixed solution; (2) subjecting the mixed solution to a scraping treatment to obtain an intermediate film; (3) The intermediate membrane is contacted and mixed with an alkaline solution to obtain the composite adsorption membrane.

9. The method according to claim 8, characterized in that In step (1), the acidic substance is acetic acid; And / or, the acidic substance is provided in the form of an acidic substance aqueous solution, and the concentration of the acidic substance aqueous solution is 0.2-0.8 mol / L; and / or, in step (3), the alkaline substance in the alkaline solution is sodium hydroxide and / or potassium hydroxide; And / or, the concentration of the alkaline solution is 5-10wt%.

10. Use of the composite adsorption membrane according to claim 6 or 7 in adsorbing heavy metal ions.

Citation Information

Patent Citations

  • Preparation method of MOFs-chitosan nanofiber composite membrane

    CN109021264A

  • Covalent organic framework composite material as well as preparation method and application thereof

    CN113522244A

  • Polyethyleneimine / chitosan composite adsorbent as well as preparation method and application thereof

    CN114749158A

  • Chitosan-covalent organic framework composite material and preparation method thereof

    CN115709054A

  • Method for preparing carboxylic acid functionalized two-dimensional covalent organic framework nanosheet in alcohol amine-propylene carbonate solution

    CN118994633A

Cited By

  • Inorganic-organic hybrid carbonyl radical luminescent material as well as preparation method and application thereof

    CN119930707A

  • An inorganic-organic hybrid carbonyl radical luminescent material, its preparation method and application

    CN119930707B